PENINGKATAN MUTU PEMBELAJARAN PKn SD MENGGUNAKAN MODEL PROJECT BASED LEARNING (PjBL) TERINTEGRASI WINDOW SHOPPING DAN APLIKASI CANVA - Fajar Satrya Pamungkas; Sutrisna Wibawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning Citizenship Education (PKn) at the elementary school level has its own challenges in providing students with an understanding of basic concepts about the state, democracy, rights and obligations, as well as social values. The difficulty of understanding abstract concepts results in low student interest in learning Citizenship Education (PKn). They are not enthusiastic and have not been actively involved in learning. One effort that can be made to improve the quality of Civics Education (PKn) learning at the elementary school level is through the implementation of the Project Based Learning (PjBL) learning model integrated with Window Shopping and the Canva Application. The aim of this research is to determine the impact of implementing the Project Based Learning (PjBL) learning model integrated with Window Shopping and the Canva Application on the quality of Citizenship Education learning at the elementary school level. The research carried out is a type of qualitative descriptive research. The techniques used in data collection are observation and documentation techniques. The data obtained is then analyzed in narrative form and makes temporary conclusions regarding the implementation of activities. The research results show that the application of the Project Based Learning (PjBL) learning model which is integrated with Window Shopping and the Canva Application can improve the quality of Civics Education (PKn) learning in elementary schools.